A study of the prevalence of various psychosocial problems of geriatric population in urban area of district-Hapur - Sisodia, Madhulika Singh; Kumar, Upender; Kumar, Gajendra (International Journal Of Community Medicine And Public Health, 2020)
Background: With advancing age, ill-health becomes a major hindrance for the well-being of the elderly. Therefore, not only physical but even psychosocial health is an important predictor for their living happily. Objective was to study the prevalence of various psychosocial problems, including dependence in study population. Methods: A cross sectional study was carried out in geriatric age group in the urban field practice areas of Department of Community Medicine, Saraswathi Institute of Medical Sciences, District-Hapur. Results: Out of 580 elderly the overall prevalence of psychosocial problems was 270 (45.6%). This includes psychosocial disorders in 34.8%, functional dependency in 12.4%, sad attitude towards life in 13.4% and low social adjustment in 8.3%. Conclusions: The psychosocial problems were higher in females as compared to males and were significantly associated with functional dependency, social adjustment and attitude towards life.